Understanding the importance of oceanic forcing on sea ice variability - Haynes, Joanne E. (Monterey, California. Naval Postgraduate School, 2010)
The rapid decline in Arctic sea ice over the past few decades has prompted scientists to better understand the factors driving sea ice variability. Analyses and syntheses of numerical model results and available observational data are presented in order to advance the understanding of critical processes and feedbacks affecting the oceanic forcing of sea ice in the western Arctic Ocean, where melt has been particularly pronounced. Results from the eddy permitting (~9km) NPS coupled ice-ocean model are analyzed for the large-scale and long-term context and compared to results from the eddy resolving (~2.3km) model over the western Arctic. Observational data from ice-tethered profilers (ITPs) and co-located ice mass-balance buoys (IMBs) are analyzed over the same region, with a focus on the entrainment of heat into the mixed layer. Results indicate that entrainment events may be a significant contributor to sea ice melt, especially in regions frequently populated by mesoscale eddies, and a limiting factor for ice growth, particularly in winter. Qualitative comparisons are made to oceanic processes occurring in the Southern Ocean to determine any similarities, especially if the current trajectory of Arctic sea ice decline continues towards a similar regime as that of its southern counterpart, where sea ice is largely seasonal and where ice melt is increasingly driven by oceanic processes. Approved for public release; distribution is unlimited. Royal Australian Navy author http://archive.org/details/understandingimp109455078